2018
DOI: 10.4172/2167-7956.1000164
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Ajawain Seeds ( Trachyspermum ammi )

Abstract: Trachyspermum ammi's seeds/leaves alcoholic and aqueous extracts were investigated for antifungal potency using disc diffusion method. Obtained result revealed that the alcoholic extracts of Trachyspermum ammi's seeds/ leaves possess good antifungal property and could be used to cure fungal infections. Such antifungal activity, may yield candidate compounds for developing new antifungal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Garlic and omam, the common culinary herbs, contain a wide array of compounds and various kinds of biological activity and hence they are being explored for the treatments of various ailments nowadays. [ 13 14 ] Antimicrobial activities of garlic[ 15 ] and omam[ 16 17 18 ] are also documented against various human pathogen, In this line the present study finds them as against M. circinelloides and comparable with the activity of Amphotericin B. Further, it is observed that though MICs of both the extracts are differing against the pathogen, both are promising and it may be due to the different constituents present in them.…”
Section: Discussionsupporting
confidence: 66%
“…Garlic and omam, the common culinary herbs, contain a wide array of compounds and various kinds of biological activity and hence they are being explored for the treatments of various ailments nowadays. [ 13 14 ] Antimicrobial activities of garlic[ 15 ] and omam[ 16 17 18 ] are also documented against various human pathogen, In this line the present study finds them as against M. circinelloides and comparable with the activity of Amphotericin B. Further, it is observed that though MICs of both the extracts are differing against the pathogen, both are promising and it may be due to the different constituents present in them.…”
Section: Discussionsupporting
confidence: 66%
“…Thymol is the major phenolic compound of T . ammi and p ‐cymene and y‐terpinene (Tabassum Khan and Jameel 2018). The main bioactive compounds of N. sativa include thymoquinone, p‐cymene, α‐thujene, longifolene, β‐pinene, α‐pinene and carvacrol (Shokri 2016).…”
Section: Discussionmentioning
confidence: 99%